Agro-morphological and molecular characterization of Amaranthus genotypes - Jonathan Siamey; Jacqueline Naalamle Amissah; Peter Amoako Ofori; Richard Adu Amoah; Eric Opoku Mensah; Daniel Ashie Kotey (PLoS ONE, 2025)
Amaranth is a climate-resilient indigenous leafy vegetable that has the potential to contribute to global food security. Owing to its high protein, essential amino acid, mineral and vitamin contents, amaranth can thrive under diverse environmental conditions including marginal soils and drought-prone areas. This study characterized 21 Amaranth accessions using a combination of agro-morphological and molecular markers to identify promising genotypes for breeding programs. Characterization was carried out at two locations using a randomized complete block design (RCBD) with three replications. Six SSR and four ISSR primers were used to assess molecular diversity. The combined analysis of variance revealed significant differences in the majority of traits measured. Frequency distribution analysis revealed the predominance of many branches, green leaf pigmentation, lanceolate and elliptical leaf shapes, and smooth leaf vein prominence. Phylogenetic association analysis grouped the genotypes into three distinct clusters. The SSR and ISSR markers significantly identified the diversity among the amaranth genotypes, with higher gene diversity values averaging 0.579 and 0.711 for SSR and ISSR, respectively. Heterozygosity average values of 0.723 and 0.601 and the polymorphism information content (PIC) average values of 0.512 and 0.665 for SSR and ISSR, respectively, were observed. The number of primary branches positively correlated with the total number of leaves (r = 0.574**) and marketable leaves (r = 0.591**). Eleven promising trait-specific genotypes were identified with respect to leaf yield, primary branches, and delayed flowering. This research revealed broad phenotypic and genotypic diversity among the amaranth genotypes and identified promising genotypes that can be exploited for the genetic improvement of Amaranthus spp. germplasm in Ghana. These findings provide valuable insights into the genetic and phenotypic diversity of Amaranthus, facilitating the selection of high-performing genotypes to harness the contribution of Amaranthus spp. in addressing food and nutrition security challenges.